RELATIONSHIP BETWEEN THE LEVEL OF EDUCATION AND KNOWLEDGE WITH THE USE OF INTRAUTERINE DEVICE CONTRACEPTIVES - Soyanita , Elin; Nataningtyas, Candra Dewi; Merita Sari, Pety (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: The high birth rate is the main reason for the need for family planning services. Data at the Semen Health Center shows low interest in IUD compared to other contraceptives, this can be caused by several existing factors. This study aims  to  determine the relationship between the level of education and knowledge of acceptors with the use of IUD (Intrauterine Device) contraceptives at the UPTD Semen Health Center, Kediri Regency East Java Indonesia. Method: This study is a quantitative study with a Cross-Sectional research plan. The sampling technique used in this study was Purposive Sampling with a sample size of 100 KB acceptor respondents in Semen District, Kediri Regency. This study was conducted in April 2024. Data collection used a questionnaire instrument. Data were analyzed using the Spearman's rho test. Result: Secondary education level (SLTA/SMK) (51%) and basic education level (SD-SMP) (43%). High knowledge, namely 83 respondents (83%). Half of the birth control acceptors are non-IUD users (74%). The results of the analysis of the Spearman's Rho test at the education level with the use of IUD contraceptives are known that the results of sig. (2-tailed) of .140, and knowledge with the use of IUD contraceptives is known as the results of sig. (2-tailed) of .038. Conclusion : There was no relationship between education level and IUD contraceptive use and there was a significant relationship between knowledge and use of birth control. Acceptors need to be proactive in seeking information about the use of IUD contraceptives through various sources such as print media, electronic media, the internet, and consultation with health professionals. This can help in choosing the right method or contraceptive for them to use.